Coupling of living cells with external electrical stimulation: A computational study - Saxena A.; Dubey A.K. (My University, 2025)
The coupling of external electric field (E-field) with living cells results in a profound effect on their metabolic activities. In order to develop a fundamental understanding of such couplings, four different electrical equivalent circuits for a living cell have been considered. As an estimate of response time of single cell in E-field, the time constant of cell and, subsequently, the influences of cell size, cytoplasmic and nucleoplasmic resistances, as well as cell and nuclear membrane capacitances, on the time constant have been analytically computed. Such computational analysis was performed by considering (a) cell membrane as leaky dielectric and (b) both the cell and nuclear membranes as leaky dielectrics, which suggest similar values (1.5 μs-5 μs), owing to the high value of nuclear membrane resistance. The variation of time constants with various electrophysical parameters of cells, such as cell size, cytoplasm and nucleoplasm resistances, as well as cell and nuclear membrane capacitances and resistances, suggests similar characteristics for both (a) and (b). To validate the proposed electric equivalent models, an analytical study for the well-known electroporation phenomenon has been carried out using similar models and the results have been observed to be consistent with the experimentally observed values. © 2018 IOP Publishing Ltd.